‘Mini, ultra, micro’ – nomenclature and cost of these new minimally invasive percutaneous nephrolithotomy (PCNL) techniques - Wright, Anna (Ther Adv Urol, 2015)
New minimally invasive percutaneous nephrolithotomy (PCNL) techniques have changed the management of renal stones. We discuss the technological advances in PCNL and explain the meaning, requirements and set up costs for each of these ‘newer’ techniques.